NUMBER OF COLIFORM BACTERIAL IN THE FECES OF BROILER OF VARIOUS AGES IN BADUNG DISTRICT - Agnes Merina Galis Afonso; I Ketut Suada; I Putu Sampurna (Buletin Veteriner Udayana, 2025)
Broiler waste generated from broiler farming is mainly in the form of chicken manure and waste water. Continuous disposal of chicken manure into the environment can pollute surrounding water sources and increase the number of microorganisms in the water. The purpose of this study was to determine the number of Coliform Bacteria in broiler feces of various ages in Badung Regency. This study used a completely randomized design consisting of 2 factors, namely chicken age 1-21 days and 22-35 days, 3 factors, namely the location of broiler farms in Petang District, Abiansemal District and Mengwi District. The volume of broiler feces samples taken was 3 grams in each farm. Bacterial growth using the spread plate method on Eosin Methylene Blue Agar media. Positive samples were characterized by pink and metallic green colonies. Data analysis into log Y. To see the difference in the number of Coliform bacteria, the variance test was carried out if there was a significant difference, then continued with the Duncan Multiple Range test. The results of the study of the number of Coliform bacteria obtained were in Petang District age 1-21 days 8.164 and age 22-35 days 7.957 and Mengwi District age 1-21 days 8.034 and age 22-35 days 7.925 and Abiansemal District age 1-21 days 8.126 and age 22-35 days 7.987. The results of variance showed that age was significantly different and location was significantly different to the number of Coliform bacteria. There was no significant interaction between age and location on the number of Coliform. It can be concluded that the number of Coliform bacteria in broiler feces in 3 locations namely Petang District, Abiansemal District, Mengwi District is significantly different.